2018
DOI: 10.1002/job.2257
|View full text |Cite
|
Sign up to set email alerts
|

Sexual harassment training effectiveness: An interdisciplinary review and call for research

Abstract: Summary Although sexual harassment (SH) training is widespread, has many important consequences for individuals and organizations, and is of demonstrated interest to researchers across a wide range of disciplines, there has never been a comprehensive, interdisciplinary attempt to identify and systematically evaluate relevant research findings. This article addresses that need in the literature. It discusses the legal context of SH training and its relevance to research issues, provides an organizing framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 83 publications
(197 reference statements)
1
78
1
Order By: Relevance
“…In particular, it is one of the few sexual harassment training studies to employ a pretest/post-test design with working HR professionals; it adds to the nascent literature examining contextual factors (Cheung et al, 2018), by considering the harassment-specific climate factor, OTSH; and is the first to show that motivation to learn mediates the effect of context on training outcomes (i.e., knowledge and attitudes). Additionally, while previous sexual harassment training studies have reported the effects of different training methods (Bonate & Jessell, 1996;York et al, 1997) and trainee characteristics (e.g., gender) (Alhejji et al, 2016;Beauvais, 1986;Blakely, Blakely, & Moorman, 1998;Bonate & Jessell, 1996;Moyer & Nath, 1998;Roehling & Huang, 2018) on training outcomes, the current study investigates an important but overlooked type of sexual harassment training and trainee audience (e.g., training involving instruction for HR managers to conduct internal investigations into sexual harassment claims). In sum, the current study advances knowledge in the field by investigating the direct effect of organizational context (i.e., OTSH) on sexual harassment training outcomes and by examining the mediating role of motivation to learn in these relationships.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, it is one of the few sexual harassment training studies to employ a pretest/post-test design with working HR professionals; it adds to the nascent literature examining contextual factors (Cheung et al, 2018), by considering the harassment-specific climate factor, OTSH; and is the first to show that motivation to learn mediates the effect of context on training outcomes (i.e., knowledge and attitudes). Additionally, while previous sexual harassment training studies have reported the effects of different training methods (Bonate & Jessell, 1996;York et al, 1997) and trainee characteristics (e.g., gender) (Alhejji et al, 2016;Beauvais, 1986;Blakely, Blakely, & Moorman, 1998;Bonate & Jessell, 1996;Moyer & Nath, 1998;Roehling & Huang, 2018) on training outcomes, the current study investigates an important but overlooked type of sexual harassment training and trainee audience (e.g., training involving instruction for HR managers to conduct internal investigations into sexual harassment claims). In sum, the current study advances knowledge in the field by investigating the direct effect of organizational context (i.e., OTSH) on sexual harassment training outcomes and by examining the mediating role of motivation to learn in these relationships.…”
Section: Discussionmentioning
confidence: 97%
“…This outcome reflects widely held, but false beliefs that serve to deny and justify sexual harassment (Lonsway, Cortina & Magley, 2008). While prior research has explored the relationship between OTSH and trainees' motivation to learn (Walsh, Bauerle, & Magley, 2013), it has not explored the extent to which motivation to learn may mediate the impact of OTSH on training outcomes including attitudes (Roehling & Huang, 2018).…”
Section: Model Overviewmentioning
confidence: 99%
“…Multiple authors have described the complexities involved in evaluating the success of sexual misconduct training (e.g., Medeiros & Griffith, 2019;Roehling & Huang, 2018;Magley et al, 2013), and this case is no exception. The SSMCAF merely aims to describe the current landscape of sexual misconduct prevalence within the organization.…”
Section: Misconduct Within a Focal Organizationmentioning
confidence: 93%
“…In contrast, for women who chose not to report a case of sexual harassment, those who had a less favourable perception of training efficacy (as compared to those with more positive views) were more likely to cite fear of retaliation, feelings of discomfort, lack of knowledge of the reporting process, and being talked out of reporting as reasons for declining to report (Buchanan et al, 2014). Broadly speaking, it is theorized that training will affect reporting indirectly through attitudinal and cultural changes (Roehling & Huang, 2018). However,…”
Section: Workplace Sexual Misconduct Training and Its Influence On Emmentioning
confidence: 99%
See 1 more Smart Citation